Children's perceptions of neighbourhood environments for walking and outdoor play. (19th May 2019) - Li, Chuo; Seymour, Michael
Abstract: Through a questionnaire and Photo-Projective Methods (PPM), this study investigates how children perceive their neighbourhood environment for walking and outdoor play. It aims to understand what features children prefer when they walk and play in their neighbourhood. A total of 86 survey packages were mailed to households with children between 8 and 12 years old; 42 survey responses were returned for a 49% response rate. Descriptive statistics and content analysis were used to analyse the survey results. The findings of this study demonstrate natural landscape elements (such as tree groupings and streams), diverse social and play areas, and scenic streets are preferred by the children aged 8–12. The findings emphasise the importance of appropriate design and management of neighbourhood environmental features, and the value of safe street design for children's walking and outdoor play.